Terug naar school. - Lagae, Johan, 1968-; Stuhlmacher, Mechthild, ....-; van der Pol, Bas, ....- (Rotterdam : NAi, 2007)
The schools programme has been poorly served by architectural circles in both the Netherlands and Flanders for many years, but the topic of school architecture's importance is back on the agenda. One of the reasons for this renewed interest can be found in the reformulation of the design task: today's information society is making new demands on education, schools are increasingly infiltrated by 'extra-curricular' functions, and ideological and pedagogical contradistinctions are fading to make way for a view of the school as a 'learning environment' focused on the individual. This issue of OASE considers how architects operate strategically under these new conditions, or how they might do this. Presenting projects by Architettura, Jeroen Geurst, Onix, Wim Cuyvers, Herman Hertzberger, SSA/xx, Ton Venhoeven and others that illustrate an engagement with the issue of the modern school, this issue also provides a platform for architects endeavouring to intervene in architecture policy for schools in a proactive way, with projects such as WiMBY! and SMaR. These modern-day strategies are alternated with a number of contributions that, by means of a close reading of plans and images of school projects from the past, reveal connections (sometimes unexpected) between design, programme, representation and ideology that are relevant to a critical reflection on today's school architecture.
Verschenen als Oase : tijdschrift voor architectuur/Journal for architecture # 72.
Keywords: Scholen -- Architectuur